PSYCHOLOGICAL FEATURES OF THE DEVELOPMENT OF COMPONENTS OF SOVEREIGN MORAL VALUES OF FUTURE PSYCHOLOGISTS - Pedorenko, Valentyna (PSYCHOLOGICAL JOURNAL, 2017)
The concept of definition of sovereign moral values of future psychologists as stable, personally notional, meaningful moral forms: examples, concepts, attitudes what give the person an opportunity to self-assess his or her own live and lives of other people are depicted in the article. The content of their structural components such as: motivation-need, cognitive, behavioral, reflexive are shown. The levels of their distinguishing of development what are based on the application of the expert estimation method are investigated. Quantitative and qualitative analysis of the results of the empirical research gives an opportunity to point out the high, medium and low levels of development of the structural components of the sovereign moral values of future psychologists. The author describes the manifestations of different levels of their development, as well as explores and analyzes the peculiarities of the development of components of the sovereign moral values of future psychologists of different courses of study and successful psychologists. The comparative analysis of the peculiarities of their development is made. The author of the article exposes the content of the motivational-need component of the sovereign moral values of future psychologists, what requires the presence of person’s needs, what determine certain motives (interests, desires) and stipulate specific goal of the development of stable, autonomous, independent moral values of the future psychologist. The content of the cognitive component consists of knowledge, the thoughts of a person about his or her own moral values, beliefs, their expediency and rationality. The behavioral component of the sovereign moral values of the psychologist implies the manifestation of stable, autonomous, independent of external circumstances of the moral values in all spheres of his life: manifestation of independence, freedom, ability to self-disclosure, constant work on oneself, search of ways for self-perfection and self-realization, protection of own honor, dignity, satisfaction of the activity what he or she engages in. The reflexive component implies awareness of the future psychologist how he or she is perceived and assessed by others, the ability to analyze, rethink their own moral knowledge, feelings, beliefs, ideals and behavior.